Language Proficiency for Careers in Tourism and Learning Different Second Foreign Languages - Nikolina Božinović; Joško Sindik (Turizam, 2013)
This paper attempts to explore differences in perceptions of students from the American College of Management and Technology (ACMT) on the importance of knowledge of various foreign languages in tourism, according to the types of second foreign languages that they learned. A total of 107 participants that are currently attending American College of Management and Technology in Dubrovnik were examined by a questionnaire, designed by the authors of this paper. Key finding in this research is the fact that students consistently consider knowledge of foreign languages in general important, while the type of second foreign language those participants learned didn’t appear to be an important factor in any of hospitality services, institutions or types of tourism. The results obtained could help in raising the awareness of the importance of the role of learning and teaching foreign languages, with a potential consequence of developing and promoting tourism in Dubrovnik and Croatia in general.